2022
DOI: 10.1186/s12879-022-07292-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of circulating microRNAs for hepatitis C virus-associated hepatocellular carcinoma: a systematic review and meta-analysis

Abstract: Aims The purpose of this study was to perform an assessment of circulating microRNAs (miRNAs) as promising biomarker for hepatitis C virus (HCV)-associated hepatocellular carcinoma (HCV-HCC) through a meta-analysis. Methods A comprehensive literatures search extended up to March 1, 2020 in PubMed, Cochrane library, Embase, Web of Science, Scopus and Ovid databases. The collected data were analyzed by random-effects model, the pooled sensitivity (SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Circulating microRNAs consist of a variety of microRNAs that are present in various extracellular fluids (e.g., plasma, serum, and whole blood) and which may be released passively during apoptosis or lysis or actively by the surviving tissue cells [ 17 ]. Circulating microRNAs exist stably in the circulatory system bound to proteins to avoid catabolism, and can be used as biomarkers for early diagnosis, therapeutic response, and prognosis of various human diseases [ 18 – 20 ]. In recent years, several studies have demonstrated the potential of circulating microRNAs as biomarkers in the early diagnosis of melanoma, but evidence-based data is still lacking [ 21 – 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Circulating microRNAs consist of a variety of microRNAs that are present in various extracellular fluids (e.g., plasma, serum, and whole blood) and which may be released passively during apoptosis or lysis or actively by the surviving tissue cells [ 17 ]. Circulating microRNAs exist stably in the circulatory system bound to proteins to avoid catabolism, and can be used as biomarkers for early diagnosis, therapeutic response, and prognosis of various human diseases [ 18 – 20 ]. In recent years, several studies have demonstrated the potential of circulating microRNAs as biomarkers in the early diagnosis of melanoma, but evidence-based data is still lacking [ 21 – 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence demonstrate miRNAs as major regulators of HCV infection including HCV replication and distinguishing chronic HCV patients, and liver disease progression such as HCC [ 34 , 35 ]. MiRNAs, especially miRNA clusters, have high diagnostic value for HCV-HCC [ 36 ]. Dysregulation of miRNAs due to HCV infection occurs via multiple pathways, such as the immune response, lipid metabolism, and cell cycle pathways [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the level of let-7 in HCC tissues caused by hepatitis C virus infection is lower than that in healthy people, and its circulating level is also negatively correlated with the degree of liver cirrhosis (47), indicating that the decreased level of let-7 family in the circulation should be related to HCV infection. Downregulation of the let-7 family leads to increased production of IL-10 by T cells, which in turn confers an important survival advantage to the virus by manipulating the host immune response (48). Subsequent studies have also found that the level of let-7i in the circulation after antiviral therapy can be used as a biomarker for the progression of HCC (32).…”
Section: Let-7 Familymentioning
confidence: 99%